2021
DOI: 10.1177/1096348021996800
|View full text |Cite
|
Sign up to set email alerts
|

How High-Performance HR Practices and LMX Affect Employee Engagement and Creativity in Hospitality

Abstract: The purpose of this article is to explore how the interactive effects of high-performance human resource (HR) practices and leader–member exchange (LMX) on employee engagement and creativity in hospitality. Based on the survey of 485 employees of hotel companies in China, the theoretical model was tested. The results showed that high-performance HR practices had a significant influence on employee engagement and creativity through psychological empowerment. In addition, the impact of high-performance HR practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…The model examined five drivers of individual employee engagement at two levels: organizationallevel drivers (leadership empowerment behavior and collaboration) and individual-level drivers (rewards and recognition, and distributive justice and procedural justice). The HLM analysis results echo prior research on the significant effect of empowerment on employee engagement (He et al, 2021). The results further confirmed that all five drivers significantly affected employee engagement.…”
Section: Theoretical Implicationssupporting
confidence: 78%
“…The model examined five drivers of individual employee engagement at two levels: organizationallevel drivers (leadership empowerment behavior and collaboration) and individual-level drivers (rewards and recognition, and distributive justice and procedural justice). The HLM analysis results echo prior research on the significant effect of empowerment on employee engagement (He et al, 2021). The results further confirmed that all five drivers significantly affected employee engagement.…”
Section: Theoretical Implicationssupporting
confidence: 78%
“…Leaders play an important part in influencing employee's workplace outcomes Shafique et al, 2020). Particularly, in service firms, employees constantly need high-quality LMX relationships to perform their services with engagement and to the fullest potential (Bani-Melhem et al, 2020;He et al, 2021). This is important because the high quality of relationships helps service employees innovate, stay competitive and motivate them to engage in citizenship behaviour (Cha and Borchgrevink, 2018).…”
Section: Relative Lmx and In-role Performance Ocb-individual And Empl...mentioning
confidence: 99%
“…Particularly, in service firms, employees constantly need high-quality LMX relationships to perform their services with engagement and to the fullest potential (Bani-Melhem et al. , 2020; He et al. , 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Studies have attempted to establish different techniques for developing employee brand engagement, refining employee brand engagement, and understanding this complex phenomenon ( Yuniati et al, 2021 ). For example, He et al (2021) examined the factors that greatly contributed to employee engagement and the results presented that equity, values, workload, communities, control, and rewards impact employee engagement. The author also discussed that transfer of information, thoughts, and ideas influence the employee brand engagement within the organization.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%